Analisis Wacana Kritis Teun A. Van Dijk terhadap Ungkapan Viral Gus Miftah di Magelang - Nabilah, Naza Azkiya (Icon: Islamic Communication and Contemporary Media Studies, 2025)
This study focuses on analyzing the discourse that emerged from the conflict surrounding Gus Miftah’s viral remark toward an iced tea seller, as well as how Teun A. van Dijk’s Critical Discourse Analysis provides an understanding of the use of language and humor. The research employs a descriptive qualitative approach, with observation and documentation used as data collection techniques. The findings reveal several discourses that developed from the case between Gus Miftah and the iced tea seller, namely the discourse of politeness and linguistic ethics in preaching, the discourse of power relations, the discourse concerning the boundaries of humor, and the discourse of image and accountability of religious figures. Through van Dijk’s analysis, it was found that the use of the word “goblok” served as a strategy to capture the audience’s attention and strengthen Gus Miftah’s authority in building an interactive relationship with the public.